Faktor-Faktor yang Berpengaruh terhadap Kejadian Demam Berdarah Dengue pada Anak Usia 6-12 Tahun Di Kecamatan Tembalang - Tuti Sandra; Muchlis AU Sofro; Suhartono Suhartono; Martini Martini; Suharyo Hadisaputro (Jurnal Epidemiologi Kesehatan Komunitas, 2019)
Background : The Dengue Fever is an infectious disease that still becomes a serious health issue since it is endemic. This research aims to explain the various factors influencing the occurrences of the dengue fever in the children age 6 to 12 years old.Methods : This research used both quantitative and qualitative methods. The quantitative research specification was the observational analytic case control design while the indept interview technique was used as the qualitative research method. The population of the study were all children age 6 to 12 years old who lived in the Semarang City. The number of the subjects were 70 cases and 70 controls and they were taken by consecutive sampling method. The data were analyzed using the bivariate and multivariate with the regression logistic method.Results : The factors proven to influence the dengue fever occurrences in the children 6 to 12 years old were the lack of the mother’s education (OR 3.031; 95%CI 1.4281-6.434; p= 0.004;), the habit of not using the insect repellent use (OR 4.293; 95%CI 1.935-9.526; p= 0.001) and the habit of not wearing long clothes (OR 2.759; 95%CI 1.240-6.138; p= 0.013).Conclusion : The factors recognized as the significant risk factors for the occurrences of the dengue fever in the children age 6 to 12 years old were the lack of the mother’s education, the habit of not using the insect repellent and the habit of not wearing long clothes. Those factors contribute 85,3% to the occurrence of dengue fever.